GRAIN SIZE AND PEBBLE MORPHOMETRY OF BIDA FORMATION SANDSTONES (NORTHERN BIDA BASIN): IMPLICATIONS FOR SEDIMENTARY PROCESSES - Jimoh, A., Yusuf; Arinde, A., Victoria; Ojo, J., Olusola; Haruna, K., Abdulrazaq; Nurudeen, K., Olasunkanmi (FUDMA Journal of Sciences, 2025)
The intracratonic Bida Basin is one of the inland sedimentary basin in Nigeria with clastic deposition. This study investigates the transportation history, maturity, and paleodepositional environments of the Cretaceous sandstones from the Bida Formation exposed at Gbugbu, Ndeji, Maganiko, and Lafiagi within the Northern Bida Basin. A sedimentological approach was employed, comprising grain size analysis (n=26) and pebble morphometry (n=149). The inclusive graphic standard deviation (sorting) values range from (1.00-1.19, 1.28-1.98, 1.04-1.28, and 0.89-1.42) respectively, indicating most of the sandstones are poorly sorted. The sandstones, especially at Gbugbu, Maganiko, and Lafiagi, are fine-skewed to near-symmetrical, while the sandstones at Ndeji are coarse-skewed. The majority of the sandstones are platykurtic with values ranging from (0.75-0.94). These variations in the sorting, skewness, and kurtosis indicate fluctuating depositional energy, mixed sources, short transportation, and environments ranging from fluvial dominance over beach settings. Morphometry indices such as the mean, flatness ratio, elongation ratio, oblate-prolate index, and maximum projection sphericity index support these environmental interpretations, with sphericity values ≥ 0.65 suggesting fluvial dominance. The roundness and sphericity of the pebbles suggest short transportation. The occurrence of beach pebbles in the Bida Formation is an indication that the sediments were deposited in an environment shared between a river and beach tidal zone since the majority of pebbles showed a bladed form in the sphericity-form diagram. The majority of the pebbles yielded a bladed compact shape with a dominating sphericity index symptomatic of fluvial sediments. .